Electronic Detection of Oxygen Adsorption and Size‐Specific Doping of Few‐Atom Gold Clusters on Graphene. Issue 24 (30th October 2018) - Scheerder, Jeroen E.; Liu, Shuanglong; Zharinov, Vyacheslav S.; Reckinger, Nicolas; Colomer, Jean‐François; Cheng, Hai‐Ping; Van de Vondel, Joris; Janssens, Ewald
Abstract: Graphene's sensitivity to adsorbed particles has attracted widespread attention because of its potential sensor applications. Size‐selected few‐atom clusters are promising candidates as adparticles to graphene. Due to their small size, physicochemical properties are dominated by quantum size effects. In particular, few‐atom gold clusters demonstrate a significant catalytic activity in various oxidation reactions. In this joint experimental and computational work, size‐selected gold clusters with 3 and 6 atoms adsorbed on graphene field‐effect transistors and their interaction with molecular oxygen are investigated. While oxygen adsorbs at both cluster sizes, there is a pronounced cluster size dependence in the corresponding doping, as demonstrated via first‐principle calculations and electronic transport measurements. Furthermore, the doping of gold cluster decorated graphene changes sign from n‐ to p‐doping upon oxygen adsorption, directly evidencing electron transfer to the oxygen molecules and hence their activation. These observations pinpoint graphene as a valuable platform to investigate and exploit size‐dependent cluster properties. Abstract : Atomically size‐selected gold clusters with three and six atoms adsorbed on graphene field‐effect transistors, and the interaction of these hybrid systems with molecular oxygen, are investigated through electronic characterization and density functional theory. There is a pronounced size‐dependence in the doping of graphene. These observations pinpoint graphene as a valuable platform to exploit size‐dependent cluster properties.